2009
DOI: 10.1111/j.1399-3038.2008.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cat keeping, allergen exposure, allergic sensitization and atopic diseases: Results from the Children of Lübeck Allergy and Environment Study (KLAUS)

Abstract: The role of cat keeping on the promotion of allergies is discussed controversially. We investigated the associations between cat keeping, allergen exposure, allergic sensitization and atopic diseases in pre-school children. A total of 606 children (5- to 6-yr old) were studied in the course of the mandatory school entrance examination. Information on doctor diagnosed asthma and allergic rhinitis, pet keeping and confounders was obtained by questionnaire. The prevalence of atopic eczema was determined by dermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 16 publications
(21 reference statements)
0
12
1
1
Order By: Relevance
“…However, in our study there was no statistical difference in the need for hospitalization for asthma between asthmatic children with or without indoor animals. This is not consistent with other studies [18,19]. Passive tobacco smoking and exposure to outdoor dust and smoke were significant risk factors in the prevalence of asthma but had no significant effect on the need for hospital admission in our study, whereas other studies showed that exposure to smoke increased the severity of asthma and the need for hospital admission [14,20].…”
Section: Risk Factors For Hospitalizationcontrasting
confidence: 99%
“…However, in our study there was no statistical difference in the need for hospitalization for asthma between asthmatic children with or without indoor animals. This is not consistent with other studies [18,19]. Passive tobacco smoking and exposure to outdoor dust and smoke were significant risk factors in the prevalence of asthma but had no significant effect on the need for hospital admission in our study, whereas other studies showed that exposure to smoke increased the severity of asthma and the need for hospital admission [14,20].…”
Section: Risk Factors For Hospitalizationcontrasting
confidence: 99%
“…Fel d 1 is carried by small particles (<5-µm diameter) that readily become airborne and remain suspended in the air for a long time. It is a ubiquitous allergen, as it has been found in indoor environments such as schools in which cats have never been kept [8]. In dogs, major allergens have been identified in saliva, epidermal scales, and urine.…”
Section: Indoor Allergensmentioning
confidence: 99%
“…Sensitization to cat allergens in childhood is thought to be a risk factor for the future development of pollinosis, asthma, and allergic eczema [4, 6]. In Japan, a survey of 504 asthma patients conducted in 1993–1994 reported that 70 % of 44 patients who kept cats and 34 % of 394 patients who had never kept cats were positive for cat-specific IgE, as indicated by CAP-RAST score ≥2 [7].…”
Section: Introductionmentioning
confidence: 99%